ChemInform Abstract: An Efficient Ultrasound‐Assisted Synthesis of N‐Alkyl Derivatives of Carbazole, Indole, and Phenothiazine. Issue 47 (6th November 2014) - Zhao, Sanhu; Kang, Jin; Du, Yuting; Kang, Jingyan; Zhao, Xiaoni; Xu, Yinfeng; Chen, Ruixi; Wang, Qianqian; Shi, Xitao
Abstract N‐Heterocycles (I), (VI), and (VIII) are alkylated under ultrasonic irradiation in the presence of KOH as a base.